Ant-Based Transmission Range Assignment Scheme for Energy Hole Problem in Wireless Sensor Networks - Ming Liu; Chao Song (International Journal of Distributed Sensor Networks, 2012)
We investigate the problem of uneven energy consumption in large-scale many-to-one sensor networks (modeled as concentric coronas) with constant data reporting, which is known as an energy hole around the sink. We conclude that lifetime maximization and the energy hole problem can be solved by searching optimal transmission range for the sensors in each corona and then prove this is an NP-hard optimization problem. In view of the effectiveness of ant colony algorithms in solving combinatorial optimization problems, we propose an ant-based heuristic algorithm (ASTRL) to address the optimal transmission range assignment for the goal of achieving life maximization of sensor networks. Experimentation shows that the performance of ASTRL is very close to the optimal results obtained from exhaustive search method. Furthermore, extensive simulations have also been performed to evaluate the performance of ASTRL using various simulation parameters. The simulation results reveal that, with low communication cost, ASTRL can significantly mitigate the energy hole problem in wireless sensor networks with either uniform or nonuniform node distribution.